WETLANDS AND THE BIODIVERSITY ISSUE - Denny, Patrick (SCHOOL SCIENCE, 2012)
A workshop on the Conservation and Sustainable Use of Floodplain Wetlands was organised by the British Deputy High Commission, British Council Division, Calcutta and the Asian Wetland Bureau, Kuala Lumpur in Calcutta in December 1993. Through discussions and interaction and presentation of case studies and papers, environmentalists from Britain, India, Bangladesh, Nepal and southeast Asia produced a statement of the problems affecting Indian floodplain wetlands and drew up action plans for their conservation and management in the states of West Bengal, Bihar and Assam. A paper presented by the British expert, Professor Patrick Denny, currently working in the Netherlands, is reproduced here.